Nilai-Nilai Karakter Cerdas dalam Kumpulan Kisah Cerdik Abu Nawas Menjebak Pencuri Versi Mulasih Tary Dan Abdul Muhammad Baiyazid - Masviva, Nadiah; Nurizzati, Nurizzati (Universitas Negeri Padang, 2024)
This research aims to discuss: (1) the value of intelligent character, an attitude of faith and piety, (2) the value of intelligent character, an honest attitude, (3) the value of intelligent character, an intelligent attitude, (4) the value of intelligent character, a tough attitude, (5) the value of intelligent character an caring attitude, Abu Nawas's Ingenious Story Group Traps Thieves Mulasih Tary and Abdul Muhammad Baiyazid's version, published in 2022. This type of research is literary research using descriptive methods. This research data is in the form of words, phrases, clauses or sentences in the form of speech and behavior of characters related to intelligent character values. Data was collected by reading and understanding the contents of the fairy tale, marking words, phrases, clauses and sentences and taking an inventory of intelligent character values. Data is analyzed through the stages of identifying and classifying data, analyzing and interpreting data, drawing conclusions and reporting the results in the form of a thesis. This research found: (1) intelligent character values, attitudes of faith and piety, indicators of faith and piety, carrying out commands and avoiding prohibitions, being grateful and sincere; (2) the value of intelligent character, honest attitude, indicators of saying what is true, acting based on the truth, being responsible, and fulfilling obligations and accepting rights; (3) intelligent character values, intelligent attitudes, indicators of logical thinking, finding solutions, creative, forward thinking and positive; (4) intelligent character values, tough attitudes, indicators of being thorough, patient, skilled, not giving up and being test-resistant; (5) intelligent character values, caring attitudes, indicators of politeness, obeying orders, deliberation, being helpful and forgiving.